2004
DOI: 10.1016/j.poly.2004.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Separation of actinides and lanthanides: crystal and molecular structures of N,N′-bis(3,5-di-t-butylsalicylidene)-4,5-dimethyl-1,2-phenylenediamine and its uranium complex

Abstract: The preparation of the tetradentate dianionic ligand N,N 0 -bis(3,5-di-t-butylsalicylidene)-4,5-dimethyl-1,2-phenylenediamine [H 2 L] is described, together with the corresponding uranium complex [UO 2 (L)CH 3 OH]. H 2 L has been found to selectively bind to a representative actinide ðUO 2 2þ Þ rather than to lanthanum (La 3+ ) due to its cavity size. Both the free ligand and uranyl complex were characterized by elemental analysis, spectroscopic methods and single-crystal X-ray diffraction. The crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…U-N imine distances are typically longer than the U-O phenolic distances, explained by Pearson's hard and soft acid-base concept [31,32]. This concept agrees well with what is observed in the compound studied, as nitrogen would be expected to be bonded less strongly to a hard acid such as (UO 2 2+ ), while oxygen has relatively A c c e p t e d M a n u s c r i p t higher base strength towards uranium [33]. As expected, the U-O phenolic and the U-N imine bond lengths are similar to those observed in previously reported dioxouranium(VI) complexes [34,35] [35,36].…”
Section: Crystal Structure Of 2bsupporting
confidence: 85%
“…U-N imine distances are typically longer than the U-O phenolic distances, explained by Pearson's hard and soft acid-base concept [31,32]. This concept agrees well with what is observed in the compound studied, as nitrogen would be expected to be bonded less strongly to a hard acid such as (UO 2 2+ ), while oxygen has relatively A c c e p t e d M a n u s c r i p t higher base strength towards uranium [33]. As expected, the U-O phenolic and the U-N imine bond lengths are similar to those observed in previously reported dioxouranium(VI) complexes [34,35] [35,36].…”
Section: Crystal Structure Of 2bsupporting
confidence: 85%
“…In this communication, we have demonstrated that the one-electron oxidation of the diamagnetic S = 0, d 8 + cannot be explained by electronic effects. Rather, they may be the result of axial coordination by water (present as impurities) and/or intermolecular interactions, which allow the stabilisation of a six-coordinate Ni III complex.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, the measured UAO ax bond distance of 1.80-1.81 Å is substantially larger than the UAO ax bond distance of 1.76 Å of aqueous species such as [UO 2 (H 2 O) 5 ] 2+ (Sémon et al, 2001). According to Kannappan et al (2004), the origin of an enlarged UAO ax bond length of 1.805 Å is a hydrogen bond OAH Á Á Á O ax with the length of 2.831 Å . The calculated FeAO distance is in line with an FeAOH bond at the apex of the Fe octahedron (Combes et al, 1989).…”
Section: Refinement Of the U(vi)-ferrihydrite Complexmentioning
confidence: 96%